Toward Interoperable SCADA: Node-RED-Based Edge Integration of Heterogeneous PLCs and IoT Devices - Smerpitak, Krit; Kaewchaiwong, Sattachai; Ukakimaparn, Prapart; Julsereewong, Amphawan; Pongswatd, Sawai (My University, 2025)
This article presents a novel approach to supervisory control and data acquisition (SCADA) design that emphasizes interoperability through edge integration, using Node-RED as an open-source programming platform deployed on an industrial edge computer. The proposed architecture integrates multiple-vendor programmable logic controllers (PLCs) and an Internet of Things (IoT) gateway at the edge layer to enable seamless interoperability across local control systems. A lab-scale case study demonstrates the feasibility of this integration, featuring four remote terminal units (RTUs) communicating concurrently with a SIMATIC IPC327G edge computer via standard protocols. Specifically, a SIMATIC S7-1200 (RTU-1), MELSEC iQ-F FX5U (RTU-2), and CompactLogix 1769-L30ER (RTU-3) control an object sorting station, a parcel sorting station, a water temperature control station, respectively, while a UG65 gateway (RTU-4) enables bidirectional data transfer between the edge computer and LoRaWAN devices. The inclusion of InfluxDB alongside Node-RED supports data logging and reporting functionalities. By distributing protocol translation, data processing, and shop-floor supervisory control to the edge layer, the architecture achieves real-time, vendor-neutral data orchestration while maintaining compatibility with a higher-level SCADA master terminal unit (MTU) or cloud system. Experimental results from both functional and performance testing confirm the system’s viability as a cost-effective, vendor-agnostic solution for modern industrial automation, offering a scalable model for multi-protocol industrial environments.
Keywords: data acquisition; Edge integration; Industrial automation; Internet of things; Interoperability; Node-RED; Programmable logic controller; Supervisory control